Linguistic Landscape in Singaraja, Bali: A Sociolinguistics of Globalization Perspective - Ni Luh Rheina Premayanti; I Made Suta Paramarta; I Wayan Swandana (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study examines the linguistic landscape of Singaraja, Bali, from a sociolinguistics of globalization perspective, focusing on how languages are represented, structured, and interpreted in public spaces. The research aims to analyze linguistic scale, indexicality, and polycentricity as reflected in public signage along Jalan Udayana, a semi-urban corridor characterized by educational, administrative, and commercial activities. Employing a descriptive qualitative approach, the study collected data from 100 public signs selected through purposive sampling. Data were obtained through systematic observation and photographic documentation, with analysis guided by Creswell’s qualitative procedures, including data organization, coding, categorization, and interpretation. The findings reveal that five sociolinguistic scales are present in the linguistic landscape: global, national, national–global, national–local, and national–local–global. Among these, the national–global scale is the most dominant, indicating a strong interaction between Indonesian as the national language and English as a global linguistic resource. This pattern suggests that public signage is not merely communicative but also symbolic, reflecting modernity, professionalism, and participation in global consumer culture. Additionally, indexical meanings embedded in language choices indicate social, economic, and cultural positioning, while the coexistence of multiple language norms demonstrates polycentricity in language use. Overall, the study highlights that the linguistic landscape of Singaraja reflects layered sociolinguistic processes shaped by globalization, where local, national, and global influences interact dynamically. The findings contribute to a deeper understanding of how language operates in semi-urban public spaces beyond tourism-driven contexts.